1999
DOI: 10.1046/j.1469-0705.1999.14020114.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of normal breast tissue and of solid breast masses using three‐dimensional ultrasound mammography

Abstract: Three-dimensional reconstruction, in particular parallel planar reformatted sections, represents a valuable adjunct to the characterization of breast masses using ultrasongraphy. Further studies are necessary to assess the validity of the present findings, particularly with regard to the rarer, more unusual types of carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1
11

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 14 publications
0
40
1
11
Order By: Relevance
“…The detection rate of the "hyperechoic rim sign" differs according to the tumor pathological type and was detected by the ABVS in 72.7% (32/ 44) of the benign lesions in the current study that is inconsistent with Rotten's study where the detection rate was 100% [8]. The cause may be that the tumors in the Rotten's study were all fibroadenomas, in contrast to the multiple types of tumors included in our study, and notably all four fibroadenomas (100%) were "hyperechoic rim sign" positive, a result that was consistent to Rotten's findings.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The detection rate of the "hyperechoic rim sign" differs according to the tumor pathological type and was detected by the ABVS in 72.7% (32/ 44) of the benign lesions in the current study that is inconsistent with Rotten's study where the detection rate was 100% [8]. The cause may be that the tumors in the Rotten's study were all fibroadenomas, in contrast to the multiple types of tumors included in our study, and notably all four fibroadenomas (100%) were "hyperechoic rim sign" positive, a result that was consistent to Rotten's findings.…”
Section: Discussioncontrasting
confidence: 99%
“…The "hyperechoic rim sign" was first reported and described in 1999 by Rotten et al [8], who observed a complete hyperechoic rim peripherally between the mass and surrounding tissues on ultrasound coronal imaging. It was considered that the "hyperechoic rim sign" has been found in most fast-growing benign tumors, and is usually absent in the image of malignant tumors that invade into or become adhesive to the surrounding tissues [9].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The detection of spiculated margins has the highest value in differentiating the breast masses. The ability of three-dimensional US of rapidly imaging the breast structures in the coronal plane has been proven to increase US specificity [5]. This is particularly true for masses located in mostly fatty breasts or adjacent to the Cooper's ligaments or the superficial fascia.…”
Section: Relevance Of Technological Innovationsmentioning
confidence: 99%
“…In the coronal plane, using the retraction/star pattern sign as an indicator for malignancy and the compression pattern sign for benignancy, a sensitivity of 91% is reported by Rotten et al [40,41], a specificity of 94%, a ppv of 87%, and an npv of 96%. In daily routine diagnostic work, 4D grey-scale US did not prove to enhance true-positive results or to reduce falsepositive results.…”
Section: Discussionmentioning
confidence: 99%